A history of early al-Andalus : the Akhbār majmūʻa : a study of the unique Arabic manuscript in the Bibliothèque nationale de France, Paris, with a translation, notes and comments /: the Akhbār majmūʻa : a study of the unique Arabic manuscript in the Bibliothèque nationale de France, Paris, with a translation, notes and comments. (2012) - Unknown
No abstract available